Qualitative and quantitative muscle ultrasound in patients with Duchenne muscular dystrophy: Where do sonographic changes begin?. (September 2020) - Vill, K.; Sehri, M.; Müller, C.; Hannibal, I.; Huf, V.; Idriess, M.; Gerstl, L.; Bonfert, M.V.; Tacke, M.; Schroeder, A.S.; Landgraf, M.N.; Müller-Felber, W.; et al.
Abstract: Objective: The number of studies investigating and understanding the disease mechanisms of Duchenne muscular dystrophy (DMD) in human clinical trials have increased substantially over the last decade. Suitable clinical instruments for the measurement of disease progress and drug efficiency are mandatory, but currently not available, especially in the youngest patients. The aim of this study was to detect a reproducible pattern of muscle involvement in early stages potentially preceding evidence of motor regression. Material and methods: A cohort of 25 DMD patients aged 1–6 years at the first presentation were examined at multiple timepoints and compared with age-matched healthy controls. Muscle ultrasound was quantified using computer-analyzed gray scale levels (GSL) and blinded visual rating, using a modified Heckmatt scale. Results: Changes in muscle echogenicity in DMD patients occurred very early, clearly preceding motor regression and in some cases, even before the motor plateau phase was reached. Visual rating and GSL identified the earliest changes in the proximal adductor magnus muscle. Conclusion: Muscle ultrasound can be used as an additional method to assess the disease progression and for decision-making in paucisymptomatic DMD patients. Sonographic changes in the ad-ductor magnus muscle seem to be the first detectable changes with a recognisable pattern. Highlights: In all patients with detectable changes in the muscle ultrasound, the adductor magnus was the first muscle involved. Changes in the adductor magnus muscle precede those in the quadriceps femoris and gastrocnemius muscles. The sonographic changes in the adductor magnus muscle were present in many cases before motor plateau phase was reached. Changes in the adductor magnus muscle clearly precede the motor decline. Detecting dystrophic degeneration via muscle ultrasound should be part of decision-making of when to start steroid therapy.